2017
DOI: 10.1016/j.adolescence.2017.05.012
|View full text |Cite
|
Sign up to set email alerts
|

The mediating role of social skills and sensation seeking in the relationship between trait emotional intelligence and school adjustment in adolescents

Abstract: Drawing upon a sample of 400 female high school students in Tehran, Iran, the present study examines the mediating role of social skills and sensation seeking in the relationship between trait emotional intelligence and school adjustment in adolescent girls. Statistical analysis revealed positive correlations between trait emotional intelligence and school adjustment; trait emotional intelligence and social skills; and social skills and school adjustment. The study also revealed a negative correlation between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 13 publications
(16 reference statements)
1
11
0
1
Order By: Relevance
“…Focusing on adolescents' school-life, some authors have found a positive and predictive association between students' TEI and their level of school adjustment, in terms of pro-social behavior, cooperation, and friendship [27,28]. Nevertheless, to our knowledge, no previous study has analyzed the relationship between students' TEI and how emotionally demanding they find school tasks which, in turn, may lead to burnout [29].…”
Section: Introductionmentioning
confidence: 97%
“…Focusing on adolescents' school-life, some authors have found a positive and predictive association between students' TEI and their level of school adjustment, in terms of pro-social behavior, cooperation, and friendship [27,28]. Nevertheless, to our knowledge, no previous study has analyzed the relationship between students' TEI and how emotionally demanding they find school tasks which, in turn, may lead to burnout [29].…”
Section: Introductionmentioning
confidence: 97%
“… 7 Social skills attributes refer to students’ cooperation, adjustment, relationship-building, and friendship-making – attributes that empower students to build strong links with their peer groups and teachers to enhance academic performance. 8 Emotional intelligence plays a vital part in students’ academic learning. Students with greater emotional intelligence are more self-confident in managing academic challenges.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the logical relationship between the development of social-emotional skills, such as those trained in this programme, and the high-value benefits to the dynamics of the school is evidenced [93][94][95].…”
Section: Discussionmentioning
confidence: 96%